2020
DOI: 10.1038/s41420-020-0289-9
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine SPARC signaling dysregulates alveolar epithelial barrier integrity and function in lung fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic scarring disease in which aging, environmental exposure(s) and genetic susceptibility have been implicated in disease pathogenesis, however, the causes and mechanisms of the progressive fibrotic cascade are still poorly understood. As epithelial-mesenchymal interactions are essential for normal wound healing, through human 2D and 3D in vitro studies, we tested the hypothesis that IPF fibroblasts (IPFFs) dysregulate alveolar epithelial homeostasis. Conditioned me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 76 publications
(79 reference statements)
2
24
0
Order By: Relevance
“…In dataset GSE92592 ( 10 ), SPARC levels are increased in IPF tissues compared with control lungs ( p < 0.01; Fig. 5 C ; Table 1 ), consistent with our recent report ( 11 ). Further analysis of GSE99621 ( 12 ) showed that SPARC expression is increased not only in scarred but also in those macroscopically unaffected (normal-appearing) regions of IPF lung ( p < 0.05; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In dataset GSE92592 ( 10 ), SPARC levels are increased in IPF tissues compared with control lungs ( p < 0.01; Fig. 5 C ; Table 1 ), consistent with our recent report ( 11 ). Further analysis of GSE99621 ( 12 ) showed that SPARC expression is increased not only in scarred but also in those macroscopically unaffected (normal-appearing) regions of IPF lung ( p < 0.05; Fig.…”
Section: Resultssupporting
confidence: 91%
“…We recently reported that paracrine SPARC signaling from IPFFs dysregulates alveolar epithelial barrier integrity ( 11 ). We therefore hypothesized that SPARC might also mediate RAS activation in ATII cells during fibroblast–epithelial crosstalk.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, AEC2 exposed to IPF fibroblast-conditioned media lead to aberrant epithelialization, a surrogate of IPF-related bronchiolization. In this study, further secretome analysis identified SPARC as key paracrine mediator of fibroblast-induced epithelial activation ( Conforti et al, 2020 ). In parallel, bronchiolar smooth muscle cell progenitors in the distal mesenchyme produce WNT-dependent FGF10, allowing distal lung to repair after injury via differentiation of bronchial stem cells ( Volckaert et al, 2011 ).…”
Section: Epithelium–mesenchyme Crosstalk In Respiratory Diseasesmentioning
confidence: 78%
“…RTqPCR was performed as previously described 3,50,51…”
Section: Reverse Transcription Quantitative Polymerase Chain Reaction (Rtqpcr)mentioning
confidence: 99%